Oxidation of Reactive Orange 16 by Copper Oxide System - Wong, Wan Yuan (2006)
A commercial activated carbon (KI7080) sample was treated by HN03 and followed by heat treatment at 500 and 700°C under a flow of N2. Three types of copper oxide supported-activated carbon catalysts were prepared using impregnation techniques. 5 wt % of Cu was loaded for each catalyst and calcined at 500QC. Samples were characterized by FTIR, XRD and nitrogen adsorption isotherm studies. The adsorption-desorption isotherms of all samples showed a iypical Type I with hysteresis loops of H',. The decolourisation of reactive orange 16 (R016) by different advanced oxidation processes was investigated. The rate of colour removal was studied by measuring the absorbance at characteristic wavelengths. The effect of CuO dose, H202 dose, W light, added AC and catalyst was studied. These parameters influenced the dewlourisation rate. The comparison between powdered and granular CuO was also studied. It was found that the dewlourisation rate increased until an optimum Hf12 dosage (60 ml of 1 M Hz02), beyond which the reagent exerted an inhibitory effect For CuO/H202 system, contribution of the leached cu2+ to ffie total colour removal by CuO/H202 can be estimated approximately 40 %. Tbe colour removal by CuOl&02 system is an adsorption/oxidation process. The effect of W on the decolourisation of R016 was in the following order: C\10/UVIH2O2 > Cu0/H2O2 > CuO/UV = CuO > UV&Q > H202 > UV. A simple kinetic model confirmed a pseudo-second order reaction for CuO, CuOM202, CuO/UV/H202, CuOIUV, UVJH202, Hz@, ACICuO/H2@, S%Cu-ACX, 5%Cu-ACN/UV/H202, 5%Cu-ACN/H202 and 5%Cu-ACN/UV systems. The AC/CuO/H202 system exhibited a lower efficiency compared to CuO/H2@ most probably due to decomposition of H202 and reduction of cu2+. The decolourisation efficiency of 5% Cu-ACN catalyst under four different conditions was observed in the following order: S%CU-ACW/UV/H~Q> S%CU-ACN/H~@> S%Cu-ACNNV = 5%Cu-ACN. 5%Cu-ACN/UV/H202 system was found to be the most efficient method on decoloun'sation of ROI 6 in this study.